Optimization and evaluation of nebivolol hydrochloride loaded transferosomes using Box-Behnken experimental design - Shelke, P V; Rachh, Punit R; Mankar, Someshwar; Amin, Saurin; Jain, Deepak (Creative Pharma Assent, 2024)
Background: This study optimizes and evaluates transferosomes containing Nebivolol Hydrochloride to enhance the drug's bioavailability and therapeutic efficacy. Ultra-deformable vesicles called transferosomes help to increase drug administration via the skin. Methodology: Using a thin-film hydration technique, beta-blocker Nebivolol Hydrochloride, which has antihypertensive properties, was added to transferosomes. To attain the ideal vesicle size (between 200 to 300 nm), entrapment efficiency, and deformability, the formulation was adjusted by adjusting the amounts of phosphatidylcholine, Span 80, and hydration time using a Box-Behnken experimental design. Particle size analysis, zeta potential measurement, and in vitro drug release tests were performed to characterize the transferosomes. Results and discussion: The optimized formulation demonstrated notable deformability, an entrapment effectiveness of 50%, and a vesicle size of 265 nm. The Box-Behnken design made it easier to evaluate the interactions between variables systematically. In vitro drug release studies showed a drug diffusion that persisted for a whole day, suggesting that transferosomes may have long-lasting therapeutic effects. Stability studies at room temperature and accelerated conditions over six months confirmed the formulation's robustness. Conclusion: The results imply that Nebivolol Hydrochloride transferosome-based delivery may be a viable strategy for improving the drug's bioavailability and effectiveness, as nearly 100% of drugs diffuse within 24 hr, perhaps leading to a breakthrough in the management of hypertension.